2005
DOI: 10.1152/ajpheart.00971.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes in adenylyl cyclases and associated decreases in relaxation responses in mesenteric arteries from diabetic rats

Abstract: Matsumoto, Takayuki, Kentaro Wakabayashi, Tsuneo Kobayashi, and Katsuo Kamata. Functional changes in adenylyl cyclases and associated decreases in relaxation responses in mesenteric arteries from diabetic rats. Am J Physiol Heart Circ Physiol 289: H2234-H2243, 2005. First published May 13, 2005; doi:10.1152/ajpheart.00971.2004.-To assess the functional change in adenylyl cyclases (AC) associated with the diabetic state, we investigated AC-mediated relaxations and cAMP production in mesenteric arteries from rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 70 publications
(106 reference statements)
0
31
0
Order By: Relevance
“…3F and 4, E and F) makes it difficult to establish the exact cause of this decline in aortic function. Studies have shown that molecular mechanisms such as diminished expression and/or activity of vascular smooth muscle cell guanylyl cyclase (1,26) or adenylyl cyclase (37,38) contribute to impaired vasodilatory responsiveness in a sedentary lifestyle and T2DM progression, similar to sedentary OLETF rats in this study.…”
Section: Discussionmentioning
confidence: 52%
“…3F and 4, E and F) makes it difficult to establish the exact cause of this decline in aortic function. Studies have shown that molecular mechanisms such as diminished expression and/or activity of vascular smooth muscle cell guanylyl cyclase (1,26) or adenylyl cyclase (37,38) contribute to impaired vasodilatory responsiveness in a sedentary lifestyle and T2DM progression, similar to sedentary OLETF rats in this study.…”
Section: Discussionmentioning
confidence: 52%
“…A single abnormality seems unlikely, however, because there may be increased cAMP hydrolysis by type 3 phosphodiesterase, reduced generation of cAMP secondary to impaired activity of adenylate cyclases types 5/6, and impaired PKA function, possibly resulting from altered catalytic and regulatory subunit expression [125][126][127][128]. Furthermore, abnormalities in other essential components of the EDHF pathway such as impaired SK Ca channel function and reduced Cx40 expression have also been described [20,208].…”
Section: Intrinsic Modulation Of the Edhf Phenomenonmentioning
confidence: 99%
“…In a model of acquired diabetes, the defect in vascular relaxation responses have been linked to impaired adenylyl cyclase function and reduced protein expression of ADCY5/ ADCY6. 12 In mice with cardiomyopathy, cardiac expression of ADCY5 or ADCY6 improves cardiac function 13,14 and survival. 15 In transgenic mice, inhibition of adenylyl cyclase activity via activation of G i␣2 results in insulin resistance.…”
mentioning
confidence: 99%